2020
DOI: 10.1088/1361-648x/aba8c9
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-harmonic approximation of lattice dynamics and thermodynamic properties of half Heusler ScXSb (x = Ni, Pd, Pt) from first principles

Abstract: We report the lattice dynamics and thermodynamic properties of ScXSb (X = Ni, Pd, Pt) half Heusler compounds. Calculations for the structural and electronic properties were performed based on the Perdew-Burke-Ernzerhof-generalized gradient approximation density functional theory. We used the linear response density functional perturbation theory for computations addressing the elastic property, lattice dynamics, and thermodynamic properties. Results for the equilibrium lattice parameter are in reasonable agree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…There are several experimental and computational studies reported in publications on half-Heusler alloys [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Nevertheless, the search for viable half-Heusler semiconductors with suitable properties for specific applications is still needed because some of the already discovered materials have limitations that hinder their suitability for certain applications.…”
Section: Introductionmentioning
confidence: 99%
“…There are several experimental and computational studies reported in publications on half-Heusler alloys [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Nevertheless, the search for viable half-Heusler semiconductors with suitable properties for specific applications is still needed because some of the already discovered materials have limitations that hinder their suitability for certain applications.…”
Section: Introductionmentioning
confidence: 99%